Differential intensity-dependent effects of magnetic stimulation on the longest neurites and shorter dendrites in neuroscreen-1 cells. (13th March 2015) - Lin, Ching-Yi; Huang, Whitney J; Li, Kevin; Swanson, Roy; Cheung, Brian; Lin, Vernon W; Lee, Yu-Shang
Abstract: Objective. Magnetic stimulation (MS) is a potential treatment for neuropsychiatric disorders. This study investigates whether MS-regulated neuronal activity can translate to specific changes in neuronal arborization and thus regulate synaptic activity and function. Approach. To test our hypotheses, we examined the effects of MS on neurite growth of neuroscreen-1 (NS-1) cells over the pulse frequencies of 1, 5 and 10 Hz at field intensities controlled via machine output (MO). Cells were treated with either 30% or 40% MO. Due to the nature of circular MS coils, the center region of the gridded coverslip (zone 1) received minimal (∼5%) electromagnetic current density while the remaining area (zone 2) received maximal (∼95%) current density. Plated NS-1 cells were exposed to MS twice per day for three days and then evaluated for length and number of neurites and expression of brain-derived neurotrophic factor (BDNF). Main results. We show that MS dramatically affects the growth of the longest neurites (axon-like) but does not significantly affect the growth of shorter neurites (dendrite-like). Also, MS-induced changes in the longest neurite growth were most evident in zone 1, but not in zone 2. MS effects were intensity-dependent and were most evident in bolstering longest neurite outgrowth, best seen in the 10 Hz MS group. Furthermore, we found that MS-increased BDNF expression and secretion was also frequency-dependent. Taken together, our results show that MS exerts distinct effects when different frequencies and intensities are applied to the neuritic compartments (longest neurite versus shorter dendrite(s)) of NS-1 cells. Significance. These findings support the concept that MS increases BDNF expression and signaling, which sculpts longest neurite arborization and connectivity by which neuronal activity is regulated. Understanding the mechanisms underlying MS is crucial for efficiently incorporating its use into potential therapeutic strategies.